Spine and Sport - de Jonge, Milko C.; Kramer, Josef (Seminars in Musculoskeletal Radiology, 2014)
The spine, in athletes is a relatively frequent origin of problems. Chronic spine problems are much more common compared to acute injuries. Chronic injuries to the spine most often occur in low-contact sports like gymnastics and are most commonly the result of overuse. Acute injuries are more common in high-speed and full contact sports and are traumatic in origin. Injuries to the spinal cord can be devastating but are fortunately very uncommon. Although imaging of the spine appears to be straightforward, any radiologist will acknowledge that the optimal imaging strategy is often unclear due to several reasons. For the cervical spine much has improved since the NEXUS and CCR studies appeared in which clear rules were defined when to image the C-spine in acute trauma situations. For the thoracic and lumbar spines such rules are not defined. Although conventional imaging has long been the primary imaging modality of choice there is ample evidence that this should be abandoned in favor of multidetector CT for the C-spine. This is reflected in the ACR criteria in which conventional imaging of tile C-spine in trauma is rated as the least appropriate imaging method. However, this is not true in children and adolescents although a strict age criterion is not defined. It is also not true for injuries to the thoracic and lumbar spine in which conventional imaging still plays a large role as primary imaging modality followed by evaluation by CT in trauma situations. The role for MRI in acute situations is increasing especially with the increasing use of the TLICS system to classify injuries of the thoracic and lumbar spine in which the evaluation of the integrity of the posterior ligamentous structures is included. For the evaluation of chronic complaints, the roles of CT and MRI are basically reversed in which MRI will become the prime imaging modality of choice after conventional imaging after which CT can be reserved for a selected patient group. The merit of the different imaging modalities will be discussed together with a spectrum of acute and chronic injuries often encountered in the spine in athletes.
Keywords: spine; athlete; sports; imaging; multidetector CT; MRI; trauma; chronic back pain